Comparison of incidence of intra uterine fetal death and its causes at an interval of five years in Kathmandu University Hospital - Tamrakar, Suman Raj; Tripathi, Priyanka (Nepal Journal of Obstetrics and Gynaecology, 2020)
Aims: To compare the incidence of intra uterine fetal death and its causes at an interval of five years. Methods: This retrospective study was conducted to compare the incidence of intrauterine fetal death and its causes during 2010 and 2011 versus 2016 and 2017. Results: A total of 4219 deliveries conducted in the year 2010 and 2011, of them 90 (2.13%) were intrauterine fetal death. Likewise altogether 5873 deliveries conducted in the year 2016 and 2017, of them 105 (1.79%) were intrauterine fetal death. Mean age of mothers with fetal death were similar (25.47±5.64 vs 25.76±5.7 years; p>0.05). Common presenting complaints were reduced/absent fetal movement, abdominal pain, pre-labor rupture of membranes and antepartum hemorrhage. The majority of women were at low risk. Fetal characteristics of the intrauterine fetal deaths were almost comparable except fetal weight. Dead fetuses weighed lower significantly in the year 2016 and 2017 (2182.78±821.04 vs 1943.62±912.19 gram; p=0.05). In both periods, majority of stillborn babies appeared to be non-dysmorphic. There were significant numbers of referred-in cases who have complications. Conclusions: The incidence of intrauterine fetal death is decreased in Kathmandu University Hospital over the years and referred-in cases are more for the obstetric care. Keywords: fetal death, fetal movements, nuchal cord, placenta